Topological controls on aluminosilicate glass dissolution: Complexities induced in hyperalkaline aqueous environments. Issue 11 (29th July 2020) - Oey, Tandré; La Plante, Erika Callagon; Falzone, Gabriel; Yang, Kai; Wada, Akira; Bauchy, Mathieu; Bullard, Jeffrey W.; Sant, Gaurav
Abstract: Fly ash, an aluminosilicate composite consisting of disordered (major) and crystalline (minor) compounds, is a low‐carbon alternative that can partially replace ordinary portland cement (OPC) in the binder fraction of concrete. Therefore, understanding the reactivity of fly ash in the hyperalkaline conditions prevalent in concrete is critical to predicting concrete's performance; including setting and strength gain. Herein, temporal measurements of the solution composition (using inductively coupled plasma‐optical emission spectrometry: ICP‐OES) are used to assess the aqueous dissolution rate of monophasic synthetic aluminosilicate glasses analogous to those present in technical fly ashes, under hyperalkaline conditions (10 ≤ pH ≤ 13) across a range of temperatures (25°C ≤ T≤45°C). The dissolution rate is shown to depend on the average number of topological constraints per atom within the glass network (nc, unitless), but this dependence weakens with increasing pH (>10). This is postulated to be on account of: (a) time‐dependent changes in the glass' surface structure, that is, the number of topological constraints; and/or (b) a change in the dissolution mechanism (eg from network hydrolysis to transport control). The results indicate that the topological description of glass dissolution is most rigorously valid only at very short reaction times (ie at high undersaturations), especially under conditions of hyperalkalinity. These findings provide an improved basis to understand the underlying factors that affect the initial and ongoing reactivity of aluminosilicate glasses such as fly ash in changing chemical environments, for example, when such materials are utilized in cementitious composites.